If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + v)(5v + 2) = 0 Reorder the terms: (5 + v)(2 + 5v) = 0 Multiply (5 + v) * (2 + 5v) (5(2 + 5v) + v(2 + 5v)) = 0 ((2 * 5 + 5v * 5) + v(2 + 5v)) = 0 ((10 + 25v) + v(2 + 5v)) = 0 (10 + 25v + (2 * v + 5v * v)) = 0 (10 + 25v + (2v + 5v2)) = 0 Combine like terms: 25v + 2v = 27v (10 + 27v + 5v2) = 0 Solving 10 + 27v + 5v2 = 0 Solving for variable 'v'. Factor a trinomial. (5 + v)(2 + 5v) = 0Subproblem 1
Set the factor '(5 + v)' equal to zero and attempt to solve: Simplifying 5 + v = 0 Solving 5 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + v = 0 + -5 Combine like terms: 5 + -5 = 0 0 + v = 0 + -5 v = 0 + -5 Combine like terms: 0 + -5 = -5 v = -5 Simplifying v = -5Subproblem 2
Set the factor '(2 + 5v)' equal to zero and attempt to solve: Simplifying 2 + 5v = 0 Solving 2 + 5v = 0 Move all terms containing v to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5v = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5v = 0 + -2 5v = 0 + -2 Combine like terms: 0 + -2 = -2 5v = -2 Divide each side by '5'. v = -0.4 Simplifying v = -0.4Solution
v = {-5, -0.4}
| 7+4(6-5x)=3-16x | | 6s-1.5s+2.25s=40.50 | | -10(x-1)=10-1x | | -7x+8y=15 | | -xy^4(7xy^2+2xy-8x)= | | 2mx^2=-x^2-8x+6 | | 2mx^2=-x-8x+6 | | u^2+6u-7=0 | | x-1=25/5 | | -f/4+20.5=12.9 | | (2m+1)x^2=0 | | 16[x+2]-8=16x+24 | | 5+3+x=27 | | 4x^7+18x^6+18x^5=0 | | 6+5+x=14 | | -9+5x=-24 | | 100+1x=(5-1)x | | -46=5x-3x | | -x^3+6x^2-3x-10=0 | | 12x+15-13-8x=0 | | 3x-8=-41 | | 3.65=x-1.4 | | 7(z-2)-3z=44 | | x-8=0.64 | | -5+2x=13 | | 7x+4=10y-7 | | 100+1x=5x-1x | | -6x^2-35x-33=0 | | 50=8+2a | | -26=5y-6 | | 6x^2+35x+33=0 | | 8x+47=8[x+5] |